A novel method for kinetics analysis of pyrolysis of hemicellulose, cellulose, and lignin in TGA and macro-TGA. Issue 34 (15th April 2015) - Zhou, Hui; Long, Yanqiu; Meng, Aihong; Chen, Shen; Li, Qinghai; Zhang, Yanguo
<x xml:space="preserve">Abstract</x> A novel peak analysis-least square method to analyze the kinetics is developed. The accuracy of this method is very good.